β-Pd3P2S8 와ANi4(PO4)3 (A=K, Rb)의 합성과 결정구조 - 임윤미 (The Graduate School, Ajou University, 2014)
The new ternary palladium thiophosphate,β-Pd3P2S8 and new nickel phosphates, ANi4(PO4)3 (A=K, Rb) have been prepared andtheir crystal structures have been determined through single crystal x-ray diffraction techniques.In the middle of searching for new alkali metal thiophosphate using the reactive halide-flux technique, we have found a new form of the previously reported α-Pd3P2S8. The crystal structure of the β-Pd3P2S8 has been determined by single-crystal X-ray diffraction.Although the same building units, square planar PdS4 and tetrahedral PS4 are found in both phases, they shows drastically different structures. While α-Pd3P2S8 adopts a two-dimensional layered structure, β-Pd3P2S8 is a cluster of formular, Pd6P4S16. This molecule has an approximate tetrahedral symmetry, four P atoms at the vertices and 6 Pd atoms at the center of each side.The classical charge balance of both compounds can be represented as [Pd2+]3[P5+]2[S2-]8.The new quaternary orthophosphates, ANi4(PO4)3(A=K, Rb) have been prepared as single crystals with the use of halide fluxes and structurally characterized by X-ray diffraction techniques. They are new members of the AM4(PO4)3 family (A=Alkali metal, M=Co, Fe, Mg, Mn, Ni).The basic building blocks of the compounds are trigonalbipyramidal NiO5, octahedral NiO6, and tetrahedral PO4. These polyhedra are connected by sharing O atoms to form the three-dimensional framework, [Ni4(PO4)3] -. An empty hexagonal channel with free diameter of about 4.8 Å is formed and the alkali metal cations, K+ or Rb+ reside in this channel through the electrostatic Coulombic interaction. The crystal field splittings of the Ni2+ ions around 2.7 eV have been observed and the distorted Ni coordinations are responsible for the bright yellow colors. The charge balance of the title compounds can be described by [A+] [Ni2+]4[P5+]3[O2-]12.
학위논문(석사)--아주대학교 일반대학원 :에너지시스템학과,2014. 2